An Overview of Basis Set Effects for Diatomic Boron Nitride Compounds (B2N(∓,0)): A Quantum Symmetry Breaking - Monajjemi, Majid; Mollaamin, Fatemeh; Samiei Soofi, Neda (MDPI AG, 2022)
The symmetry breaking (SB) of B2 not only exhibits an energy barrier for ionic or neutral forms dependent on various basis sets but it also exhibits a few SBs due to the asymmetry stretching and bending mode interactions. SB obeys the mechanical quantum theorem among discrete symmetries and their connection to the spin statistics in physical sciences. In this investigation, the unusual amount of energy barrier of SBs appeared upon the orbit–orbit coupling of BNB (both radical and ions) between transition states and the ground state. Our goal in this study is to understand the difference among the electromagnetic structures of the (B2N(∓,0)) variants due to effects of various basis sets and methods and also the quantum symmetry breaking phenomenon. In the D∞h point group of (B2N(∓,0)) variants, the unpaired electron is delocalized, while in the asymmetric C∞v point group, it is localized on either one of the B atoms. Structures with broken symmetry, C∞v, can be stable by interacting with the D∞h point group. In viewpoints of quantum chemistry, the second-order Jahn–Teller effect permits the unpaired electron to localize on boron atom, rather than being delocalized. In this study, we observed that the energy barrier of SB for BNB increases by post HF methods.
Keywords: MESP (EP); boron nitride cages; Physics; QC1-999; dipole moment; hyperfine properties; EPR-II and III; Chelp G; 7. Clean energy